Lower Physical Activity Is Associated With Higher Intermuscular Adipose Tissue in People With Type 2 Diabetes and Peripheral Neuropathy - Tuttle, Lori J. (American Physical Therapy Association, 2011)
BACKGROUND: Increased lipid accumulation in skeletal muscle has been linked to insulin resistance, impaired muscle performance, and impaired physical function. It is unclear whether physical activity is associated with lipid content in skeletal muscle, muscle performance, or overall physical function. OBJECTIVE: The purpose of this study was to characterize physical activity levels (average daily step count) in a sample of people with diabetes and peripheral neuropathy and to determine the relationship among step count, intermuscular adipose tissue volume (IMAT), muscle performance (peak torque, power), and physical function. DESIGN: A cross-sectional design was used in this study. METHODS: Twenty-two people with diabetes and peripheral neuropathy (15 men and 7 women, mean age=64.5 years [SD=12.7], and mean body mass index=33.2 kg/m(2) [SD=6.4]) participated. Average daily step count, glycosylated hemoglobin, modified 9-item Physical Performance Test scores, Six-Minute Walk Test distance, calf intermuscular adipose tissue volume (via magnetic resonance imaging), and isokinetic dynamometry of the ankle muscles were recorded. RESULTS: Average daily step count was 7,754 (SD=4,678; range=3,088–20,079). Five participants had an average daily step count greater than 10,000. Average IMAT volume was 84 cm(3) (SD=88). Greater average daily step count was associated with younger age (r=−.39, P<.05) and with lower IMAT volume in the calf (r=−.44, P<.05). Lower IMAT volume was associated with greater muscle performance (r=−.45) and physical function (r=−.43 to −.48). LIMITATIONS: The sample in this study may be biased toward people with high levels of activity because participants were recruited for an exercise study. The results should not be generalized to people taking fewer than 3,000 steps/day or to those with a current foot ulcer, peripheral arterial disease, or severe foot deformity or amputation or who weigh more than 136 kg (300 lb). CONCLUSIONS: Average daily step count was inversely related to IMAT, and IMAT was inversely related to muscle performance and overall physical function. In addition, we found that people with diabetes and peripheral neuropathy and without severe foot deformity appear to be able to take a large number of steps per day.